2004
DOI: 10.1038/sj.gt.3302280
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific gene expression using the survivin promoter is further increased by hypoxia

Abstract: Increasing evidence indicates that survivin, an inhibitor of apoptosis protein (IAP), is expressed in human cancer cells but is absent from most normal adult tissues. Here, we examined the feasibility of using a survivin promoter (Sur-P) to direct therapeutic expression of a proapoptotic gene specifically in human tumor cells. First, we demonstrated that this promoter was highly active in human tumor cells but not in normal cells. Second, we found that Sur-P activity was upregulated by hypoxia in tumor cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 42 publications
5
79
2
2
Order By: Relevance
“…[39][40][41] The expression of this gene correlates with grade and is present in 90% of glioblastomas. The activity of this promoter is enhanced by hypoxia, 42 commonly found in rapidly growing tumors like high grade gliomas. Survivin seems to play an important role in the oncogenesis and progression of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] The expression of this gene correlates with grade and is present in 90% of glioblastomas. The activity of this promoter is enhanced by hypoxia, 42 commonly found in rapidly growing tumors like high grade gliomas. Survivin seems to play an important role in the oncogenesis and progression of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In this study, we used the PTCH1 gene promoter to construct a transgenic vector. It has been recently reported that there are seven alternative first exons of PTCH1 (exon 1a, exon 1a 0 , exon 1b, exon 1c, exon 1c 0 , exon 1d and exon 1e), which are differentially regulated by independent promoters in various normal and tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the results of this study show that HRE sequences plays an important role in expression of its upstream genes in hypoxic conditions, which is a common phenomenon of solid tumors (33). Based on this condition, HRE sequence can be considered as a desirable way in targeting of cancer cells for gene therapy.…”
Section: Discussionmentioning
confidence: 93%